In vitro dissolution and release kinetics of multisource ciprofloxacin 500 mg tablets in West Gondar, Ethiopia: Implications for interchangeability and regulatory oversight - Tewodros Denekew Haile; Ayenew Ashenef; Chilot Abiyu Demeke; Yeniewa Kerie Anagaw; Abibo Wondie Mekonen; Minichil Chanie Worku; Asnakew Mulaw Beirhun; Yesuneh Tefera Mekasha; Melaku Getahun Feleke (PLoS ONE, 2026)
Background In vitro dissolution is a critical quality control test in pharmaceutical development, used to measure the rate and extent at which an active pharmaceutical ingredient (API) is released from solid dosage forms, such as tablets, into solution under standardized conditions. It serves as a predictive tool for in vivo drug behavior, providing insights into drug release mechanisms and ensuring the development of robust, effective, and consistent products. Despite its importance, data on dissolution performance remain limited for certain drugs. As a rapid, reliable, and cost-effective method to estimate drug absorption, this study focused on evaluating the dissolution profiles of different brands of ciprofloxacin 500 mg tablets and applying kinetic modeling to support regulatory decision-making. Methods Twenty samples of ciprofloxacin 500 mg tablets were collected from retail outlets in six selected sites of the West Gondar Zone including Humera, Mai Kadra, Metema, Gendawuha, Kokit, and Midregenet towns between January and July 2022. The samples were obtained from purposively selected outlets using prescription papers issued by the University of Gondar Comprehensive Hospital, following a mystery shopper approach in line with WHO (2015) strategies. All collected samples were transported to the Ethiopian Food and Drug Authority (EFDA) laboratory and conducted as per USP specification. The amount of ciprofloxacin released was quantified using UV-Vis spectrophotometry at 276 nm. While the onset of pharmacological action was not directly measured, the Mean Dissolution Time (MDT) values suggested differences in release rates, which may influence the onset of action in vivo were considered. Dissolution profiles were evaluated using both model-independent parameters (difference factor f₁, similarity factor f₂, dissolution efficiency, and mean dissolution time) and model-dependent kinetics. Results were presented in tables, figures, and narrative form. Results All of the included tablet brands complied with single-point dissolution study test, as their Active Pharmaceutical Ingredient release were greater than 80% within the specified 30 minutes time frame according to USP standards. Only 4 brands (21.05%) met the f1/f2 similarity criteria. However, fifteen brands (78.95%) were not interchangeable with the comparator, as the difference factors (f1) were greater than 15% and the similarity factor (f2) were less than 50%. The mean dissolution time values ranged between 1.02 and 7.16 minutes, and the results showed that four of the twenty brands (4/20) exhibited the fastest dissolution rate and onset of action. The evaluated brands followed the Korsmeyer-Peppas and Weibull curve approach (the highest coefficient of determination) for the release of drug substances from the dosage forms. Conclusion The study reveals that while all tested ciprofloxacin 500 mg tablet brands complied with USP single-point dissolution criteria, only 21.05% met the similarity factor (f₂) and difference factor (f₁) standards for interchangeability with the comparator product. Significant variability in dissolution profiles among brands raises concerns regarding bioequivalence and potential implications for therapeutic efficacy and antimicrobial resistance. These findings underline the necessity for enhanced regulatory oversight, including routine dissolution profiling and, where appropriate, in vivo bioequivalence studies to ensure the quality and interchangeability of multisource ciprofloxacin products in Ethiopia and similar settings.